Pollution Status of Jodhpur Town-Its Geology and Human Activities - Menaria, K.L.; Sharma, Deepshikha (Asian Journal of Chemistry, 2012)
Jodhpur is the second largest city of Rajasthan situated at the edge of Thar Desert. The old walled city or Jodhpur city has eight gates of which Jalori gate and Sojati gate on the south are surrounded by the busiest commercial centres of city. The new city is currently expanded to the south and east of the old city. Continuous industrial growth and increasing population of Jodhpur city polluting its water resources including natural age old water bodies as well as new resources though the drinking water link from canal from Indira Gandhi Nahar Main Canal. The human activities as well as the geology of the area are adversely affecting the drinking water quality of Jodhpur. The intensive study under taken has been carried out to identify the causes for redresses to this problem. For this purpose the city of Jodhpur have have been divided into four rational zones. North-West, North-East, West-South and East-South. From these four zones we have collected water samples and analyzed their physical and chemical parameters. Geological aspects of Jodhpur city have also been incorporated to suggest effective redressing measures of the current problem.